2016
DOI: 10.1245/s10434-016-5328-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact that Timing of Genetic Mutation Diagnosis has on Surgical Decision Making and Outcome for BRCA1/BRCA2 Mutation Carriers with Breast Cancer

Abstract: Background Deleterious BRCA mutation carriers with breast cancer are at increased risk for additional breast cancer events. This study evaluated the impact that timing of identification of BRCA+ status has on surgical decision and outcome. Methods The authors reviewed all BRCA carriers at their institution whose breast cancer was diagnosed between January 1996 and June 2015. Patient surveys, medical records, and institutional databases were used to collect data. Differences in surgical choice were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 29 publications
4
36
2
2
Order By: Relevance
“…When evaluating BRCA known pathogenic mutation carriers with newly diagnosed unilateral stage 0–III breast cancer ( n = 63), BRCA pathogenic mutation carriers had expectedly high rates of TM + CPM of (83%) compared with lumpectomy (13%) or TM alone (5%). 4 In comparison, in the average risk breast cancer population at Mayo Clinic Rochester (excluding patients with BRCA VUS or BRCA deleterious mutation), 25% chose TM + CPM compared with 51% lumpectomy and 24% TM. 5 Comparison of these two groups to our BRCA VUS carriers who had known VUS status before surgery demonstrates similar rates of prophylactic mastectomy between those with a VUS and those with no known pathogenic mutation (22 vs. 25%, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating BRCA known pathogenic mutation carriers with newly diagnosed unilateral stage 0–III breast cancer ( n = 63), BRCA pathogenic mutation carriers had expectedly high rates of TM + CPM of (83%) compared with lumpectomy (13%) or TM alone (5%). 4 In comparison, in the average risk breast cancer population at Mayo Clinic Rochester (excluding patients with BRCA VUS or BRCA deleterious mutation), 25% chose TM + CPM compared with 51% lumpectomy and 24% TM. 5 Comparison of these two groups to our BRCA VUS carriers who had known VUS status before surgery demonstrates similar rates of prophylactic mastectomy between those with a VUS and those with no known pathogenic mutation (22 vs. 25%, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical choices of patients with breast cancer diagnosed with a BRCA1 or BRCA2 variant of uncertain significance compared with breast cancer patients at Mayo Clinic Rochester with known BRCA1 or BRCA2 deleterious mutations and breast cancer patients with no known mutation or variant 4,5 …”
Section: Figmentioning
confidence: 99%
“…It is possible that the lack of recognition regarding the treatment potential of TFGT among participants was due, in part, to the ways in which this technology is mobilized in the clinic. In the case of breast cancer, the treatment or curative response is commonly combined with preventive measures in the form of bilateral mastectomy (Chiba et al 2016 ). Thus, it is not surprising that patients might conflate treatment and prevention in their accounts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in women presenting with primary breast cancer, bilateral mastectomy is often selected for BRCA carriers because the risk of ipsilateral or contralateral breast cancer remains high. 59 Although in vitro studies found that BRCA-mutated cell lines were exquisitely sensitive to platinum agents, clinical studies preferentially selecting platinum agents in BRCA-mutated breast cancers are inconclusive. 60 Additional Cancer Risk and Surveillance Germline pathogenic mutations in the BRCA genes are also associated with an increased risk of prostate cancer, uveal melanoma, pancreaticobiliary cancer (Table 1).…”
Section: Risk-reducing Medicationsmentioning
confidence: 99%